Effect of cellulose nano fiber (CNF) on fatigue performance of carbon fiber fabric composites. (September 2015) - Shao, Yongzheng; Yashiro, Tomoya; Okubo, Kazuya; Fujii, Toru
Abstract: The effect of cellulose nano fibers (CNF): micro-fibrillated cellulose and bacteria cellulose fibers were investigated on the fatigue life of carbon fiber (CF) fabric/epoxy (EP) composites. Epoxy used as the matrix was physically modified with CNF in advance before fabricating the laminates. The high cycle fatigue strength was significantly improved at 0.3 wt% CNF. There exists an appropriate CNF content which makes the fatigue life longest. An increase of adhesive strength between CF and matrix results due to physical modification with CNF. The adhesive strength much increases with increasing the CNF content. Almost no interfacial debonding occurs at 0.8 wt% CNF content when CF breakage takes place. On the other hand, some debonding occurs along CFs from the breaking point at 0.3 wt% CNF. Debonding is more significant in the case of no CNF addition to the matrix. An appropriate interfacial strength brought at 0.3 wt% CNF is the key of fatigue life extension.